Two-phase expansion processes in heat pump - ORC systems (Carnot batteries) with volumetric machines for enhanced off-design efficiency - Weitzer, Maximilian; Müller, Dominik; Karl, Jürgen (Renewable Energy, 2022)
Carnot batteries enable novel perspectives for decarbonizing the energy sector as an emerging technology for electrical energy storage. A power-to-heat process stores excess electrical energy as thermal energy which is transferred back to electrical energy on demand by a power cycle. This paper focuses on Carnot batteries by means of heat pumps and organic Rankine cycles (HP-ORC systems) as these systems combine the advantages of technically mature components, effective integration of heat sources and low-cost scalable storage. In combi-nation with low-enthalpy geothermal heat, Carnot batteries offer an efficient synthesis of electrical energy storage and upgrading of low-enthalpy geothermal energy. Previous works highlighted that two-phase expansion can enhance the efficiency of heat recovery cycles. The present paper discusses partial evaporation and flash evaporation in Carnot batteries based on organic Rankine cycles and organic flash cycles (OFC) with volumetric machines as they enable two-phase expansion processes. The three investigated cycles ORC, OFC and OFC with two-phase expander are systematically analyzed in three steps. First, the potential cycle performances are identified without restrictions of volumetric machines. Afterwards, the effects of under-and over-expansion due to fixed built-in volume ratios are taken into account. Finally, a validated screw expander model is utilized to determine the performance of the three cycles in off-design conditions. The results show that the vapor quality of the partially evaporated ORC as well as the flash pressure ratio of the OFC both indicate a specific optimum depending on the storage temperature. The fixed built-in volume ratio of volumetric machines limits the effi-ciency of partial evaporation in the ORC due to strong under-expansion. Notably, the built-in volume ratio does not affect the optimal flash pressure ratio in the OFC. Partial evaporation increases the power output at the cost of efficiency which can be utilized during temporary peak loads. The ORC yields higher efficiencies than the basic OFC in all operating conditions due to the throttling losses of the OFC. Contrarily, the OFC with two-phase expander increasingly outperforms the ORC with rising storage temperature spread. This advantage increases in part load conditions as the OFC becomes less sensitive to the flash pressure ratio. Hence, this facilitates the control of flash pressure ratio and enables advantageous efficiencies. Thus, partial evaporation and flash evap-oration can enhance the performance of Carnot batteries throughout a wide operational range.
CRIS-Team WoS Importer:2022-10-14